Exploring plant-microbe interactions in adapting to abiotic stress under climate change: a review - Muhammad, Ali; Kong, Xiangjun; Zheng, Shuaichao; Bai, Na; Li, Lijie; Khan, Muhammad Hafeez Ullah; Fiaz, Sajid; Zhang, Zhiyong (Frontiers in Plant Science, 2024)
Climatic change and extreme weather events have become a major threat to global agricultural productivity. Plants coexist with microorganisms, which play a significant role in influencing their growth and functional traits. The rhizosphere serves as an ecological niche encompassing plant roots and is a chemically complex environment that supports the growth and development of diverse plant-interactive microbes. Although plant-microbe interactions have been extensively investigated however, limited exploration have been made how abiotic stresses affect the structure and assembly of microbial communities in the rhizosphere. This review highlights climate change influence on plant growth, functional traits, and microbial communities. It explores plant mechanisms for mitigating abiotic stress, such as removing reactive oxygen species (ROS), regulating antioxidant activity and indole-3-acetic acid (IAA) production, and controlling growthinhibitory ethylene levels through colonization by bacteria producing ACC deaminase.Additionally, we elaborated the systematic communicatory network steered by hormonal crosstalk and root exudation, which can modulate and initiate the dialogues between plants and surrounding microbes. This network ultimately promotes the chemotactic movement of microbes towards the rhizosphere, facilitating their early colonization. Finally, we reviewed the recent advancements for understanding how plant-microbe interactions foster resilience under climate stress.